The New Worlds of Edgard Varèse: A Symposium - Van Solkema, Sherman; Carter, Elliott 1908-2012; Chou, Wen-Chung 1923-2019; Morgan, Robert P. (Brooklyn Brooklyn College, 1979)
Van Solkema, S. Foreword.--Carter, E. On Edgard Varèse.--Morgan, R. P. Notes on Varèse's rhythm.--Chou Wen-chung. Ionisation: the function of timbre in its formal and temporal organization.--Discussion.
"This volume had its origin in a symposium on Varèse's music that was held at the City University of New York in April 1977."
Keywords: Varèse, Edgard -- 1883-1965; Composer; Musical analysis